Ultra-processed food consumption is associated with increase in fat mass and decrease in lean mass in Brazilian women: A cohort study - Rudakoff, Lívia Carolina Sobrinho; Magalhães, Elma Izze da Silva; Viola, Poliana Cristina de Almeida Fonseca; de Oliveira, Bianca Rodrigues; da Silva Coelho, Carla Cristine Nascimento; Bragança, Maylla Luanna Barbosa Martins; Arruda, Soraia Pinheiro Machado; Cardoso, Viviane Cunha; Bettiol, Heloisa; Barbieri, Marco Antonio; Levy, Renata Bertazzi; da Silva, Antônio Augusto Moura (Frontiers in Nutrition, 2022)
Objective To investigate the association between ultra-processed food consumption at 23–25 years of age and measurements of body composition–fat mass, fat mass distribution and lean mass at 37–39 years of age in Brazilian adults. Methods 1978/1979 birth cohort study conducted with healthy adults from Ribeirão Preto, São Paulo, Brazil. A total of 1,021 individuals participated in the fat mass analysis (measured by air displacement plethysmography) and 815 in the lean mass analysis and fat mass distribution (assessed by dual energy X-ray absorptiometry). Food consumption was evaluated by a food frequency questionnaire. Food items were grouped according to the level of processing as per the NOVA classification. Ultra-processed food consumption was expressed as a percentage of total daily intake (g/day). Linear regression models were used to estimate the effect of ultra-processed food consumption (g/day) on body mass index, body fat percentage, fat mass index, android fat, gynoid fat, android-gynoid fat ratio, lean mass percentage, lean mass index and appendicular lean mass index. Marginal plots were produced to visualize interactions. Results The mean daily ultra-processed food consumption in grams was 35.8% (813.3 g). There was an association between ultra-processed food consumption and increase in body mass index, body fat percentage, fat mass index, android fat and gynoid fat and decrease in lean mass percentage, only in women. Conclusion A high ultra-processed food consumption is associated with a long-term increase in fat mass and a decrease in lean mass in adult women.